Green Trust as Mediator in Green Sharing Intention of Palmyra palm Packaging among Generation Z - Maria Augustin Lopes Amaral; Andrian Haro; Adrianus Ketmoen; Apryanus Fallo; Engelbertus G. Ch. Watu; Clarisa Margaretha Ang; Elisabeth Adelia Merdeka Wati Gani (Universitas Bina Sarana Informatika, 2025)
This study examines how perceived credibility, eco-literacy, and environmental awareness shape green trust and ultimately increase green sharing intention toward environmentally friendly packaging made from palmyra palm in the context of Generation Z in Kupang. The aim is to emphasize the central role of green trust as a psychological bridge between perception, knowledge, and awareness with green information sharing behavior that has advocacy value. The method used is a quantitative survey based on an attitude scale questionnaire, with analysis using Partial Least Squares Structural Equation Modeling. This study involved 144 respondents. The results show that green trust directly drives green sharing intention, perceived credibility directly drives green sharing intention, while perceived credibility, eco-literacy, and environmental awareness strengthen green trust; subsequently, green trust mediates the influence of these three factors, thereby driving stronger sharing intentions. In the context of palmyra palm packaging, trust provides psychological legitimacy to sustainability claims and channels environmental awareness impacts through more stable beliefs. Theoretically, this study enriches the green marketing literature by introducing an integrated framework that positions green trust as a mediating mechanism linking credibility, ecological literacy, and awareness with green sharing intentions, while expanding the discourse that previously focused more on green purchasing intentions. Practically, these findings provide concrete guidance for companies and policymakers to strengthen transparent communication strategies, develop ecological literacy programs, and intensify environmental awareness campaigns to encourage consumer advocacy and expand the adoption of sustainable palm based packaging as an alternative to single-use plastics.